Pengaruh Customer Review terhadap Keputusan Pembelian Marketplace - Didit Darmawan; M. Akmal Maulidi Zam-Zami (Pusat Riset dan Inovasi Nasional, 2026)
The development of the digital market in Indonesia has shifted the dynamics of consumer behavior, particularly in the context of online transactions through marketplaces. One prominent phenomenon is consumers' increasing reliance on online customer reviews as a primary source of information before making a purchase, given the limited physical access to assess products in person. This study seeks to examine the extent to which customer reviews shape purchasing decisions on marketplace platforms. A qualitative approach was chosen as the primary method, with data obtained through a literature review of relevant journals and articles. The study's results confirm that online customer reviews significantly contribute to purchasing decisions; credible, positive, and informative reviews facilitate information search, evaluation of alternatives, and strengthen perceptions of trust in products and sellers. The implications of these findings suggest that strategic review management by sellers and marketplace administrators can increase consumer confidence, product visibility, competitiveness, and transaction sustainability. In conclusion, customer reviews serve not only as a source of information but also as a crucial instrument in stimulating purchasing decisions, building consumer trust, and strengthening a product's position in the digital commerce ecosystem.